A Systematic Review of the Causes and Effects of Variation Orders in the Sustainable Construction Industry in Developing Countries - Amzafi, Nurhadirah; Ishak, Siti Aisyah; Abdul Rahim, Mustaqqim; Amlus, Muhammad Harith; A. Rani, Hafnidar; Tamalkhani; Mokhtar, Hamizah; Ayob, Afizah (International Journal of Integrated Engineering, 2024)
Variation orders are a frequent occurrence in construction. It is inevitable, but it can be controlled to minimise the cost, time overrun, and enhance the quality of work. This systemic review compiles more than 80 articles of various constructions between period of 2009 to 2022, with a focus on the similarities and differences in variation orders between developing and developed countries’ insight towards sustainable construction projects. A review of the existing literature identified that the common cause of variation order from twelve countries is the owner originated variations, change in design by consultant, error and omission in design, and lack of coordination between consultant and contractor. Out of the listed thirty causes of variation order the effects lead to affected work progress, increase in project cost, and delay in payment. The developing countries face different challenges due to economic and political instability and lack of resources, skills and experience. Even though the unbalance ratio between stakeholders could bring biased to overall findings, this review provides useful directions to construction professionals and policymakers. These findings not only will reduce the unfavourable effects but also by suggesting the intention of restoring factors of environment, economic and social sustainability in the construction industry.